Neo-Gothic styled stained glass window - Mumbai Archive Project (Jio Institute, 2024)
Gothic architecture went through a revival in the late 19th century and became very popular in Mumbai through the works of architects like Frederick Stevens. The club building was likely built in or around the same period, which has certain Gothic revival elements. For example, a distinctive feature of the neo-Gothic architecture is the use of stained glass windows, which cast colourful light on the interior of the building.